Airborne Gold Nanoparticle Detection Using Photoluminescence Excited with a Continuous Wave Laser. Issue 11 (November 2021) - Samuelsson, Per; Snellman, Markus; Magnusson, Martin H.; Deppert, Knut; Aldén, Marcus; Li, Zhongshan
We report the observation of photoluminescence emission from airborne gold, silver, and copper nanoparticles. A continuous wave 532 nm laser was employed for excitation. Photoluminescence from gold nanoparticles carried in a nitrogen gas flow was both spectrally resolved and directly imaged in situ using an intensified charge-coupled device camera. The simultaneously detected Raman signal from the nitrogen molecules enables quantitative estimation of the photoluminescence quantum yield of the gold nanoparticles. Photoluminescence from metal nanoparticles carried in a gas flow provides a potential tool for operando imaging of plasmonic metal nanoparticles in aerosol reactions. Graphical Abstract